Dietary patterns and metabolic syndrome components in women with excess weight 18 to 45 years old - Zugey Hernández-Ruiz; Sonia Rodríguez-Ramírez; Sonia Hernández-Cordero; Eric Monterrubio-Flores (Instituto Nacional de Salud Pública, 2018)
Objective. To analyze the association between dietary patterns and metabolic syndrome (MS) components in adult women with excess weight. Materials and methods. Cross-sectional study with anthropometric, dietary, biochemi- cal and blood pressure data. Dietary patterns were identified by factor analysis and multiple logistic regression models were used to analyze associations. Results. The prevalence of altered glucose was 14.6%, of hypertriglyceridemia 40.4%, of altered concentration of high density lipoprotein cholesterol (HDLc) 45.0%, hypertension 4.6% and MS 30%. The pattern with high consumption of corn tortillas, meats and legumes, was associated with less possibility of hyperglycemia (OR= 0.62; 95%CI 0.39-0.98). The pattern with high consumption of sweet and salty snacks, milk, rice, soaps and pasta, was inversely associated with the possibility of low HDLc concentration (OR= 0.76; 95%CI 0.60-0.97). Conclusions. A dietary pattern with greater consumption of legumes, meats and corn tortillas was associated with less possibility of having hyperglycemia.